Community building: revitalizing the nation's public housing. - Naparstek, Arthur; Smith, Robin; Dooley, Dennis (Journal of Housing & Community Development)
In order to achieve their public objective in an age of diminishing resources, public housing managers are increasingly making use of methods that contain a community-building perspective. Community building is an approach to combating poverty that works by creating social and human capital. Community building proposes that residents assume leadership and responsibility instead of being passive recipients of services. Details of some community-building schemes and of the principles of community building are provided.